A short review on the potential of fruits for the production of vinegar with functional properties - Fan, Hui Yin; Lee, Jau Shya; Mansoor Abdul Hamid; Hasmadi Mamat; Md Jahurul Haque Akanda; Siti Faridah Mohd. Amin (UniSE Press, 2021)
Vinegar is known for its functional properties due to its health-conferring benefits. Vinegar is a natural food product that is produced from carbohydrate sources via alcoholic and acetic fermentation. Fruits are of great interest to be used in the making of vinegar due to their high contents of carbohydrates and health-associated compounds. This paper reviews the production of fruit vinegar as potential functional foods. Recent studies found that the fermentation of various fruits produced vinegar with reduced sugar content and increased acidity containing acetic acid predominantly. Results also revealed the enhanced antioxidant capacities and antimicrobial properties of some fruit vinegar. Hence, the use of fruits offers potential in the production of vinegar with functional properties.